Peningkatan Hasil Belajar IPS dengan Menggunakan Pendekatan Kontekstual Siswa Sekolah Dasar kelas V SDN 011 Bukit Melintang - Nani Zuriati; Wida Rianti; Putri Hana (Jurnal Pendidikan Tuntas, 2023)
This study is based on the low learning outcomes of students in IPS subjects in class V SDN 011 Bukit Melintang. One solution to solve this problem is to use the Contextual approach. The purpose of this study is to describe the improvement of IPS learning outcomes of ethnic and cultural diversity in Indonesia by using the contextual approach of grade V students SDN 011 Bukit Melintang. This Research Method is Classroom Action Research (PTK) which implemented in two cycles. The study was conducted from Augustl to September 2017. The subjects of this study were the students of grade V of SDN 011 Bukit Melintang which amounted to 20 people, with the number of male students 9 people and female students 11 people. Data collection techniques used in this study are the techniques of observation, documentation, and tests. Based on the research results can be concluded that in the first cycle is still quite average with an average of 70.50, then from 20 students only 11 students or 55% who achieve mastery individually. Student learning outcomes in cycle II is good with an average of 76.67 and 17 students complete or 85% who achieve mastery individually. Thus it can be concluded that by using a contextual approach can improve the learning outcomes of ethnic and cultural diversity of the students in grade V SDN 011 Bukit Melintang. Keywords: Learning Result, contextual approach, social education science